Одно замечание по поводу теорем Пэли и Стейна - Кириллов, С.А. (Український математичний журнал, 2000)
Показано, що в умовах теорем Пелі та Стейпа систему з обмеженими нормами в L∞ можна замінити системою з обмеженими нормами в ВМО. We show that, under the conditions of the theorems of Paley and Stein, a system with bounded norms in L∞ can be replaced by a system with bounded norms in the space of functions of bounded mean oscillation.